2019
DOI: 10.1109/access.2019.2951366
|View full text |Cite
|
Sign up to set email alerts
|

Dominance in Visual Space of ASD Children Using Multi-Robot Joint Attention Integrated Distributed Imitation System

Abstract: The focus of this research is to study: 1) the distribution of joint attention of autistic (ASD) children in their left and right visual space, 2) the corresponding dominance of either left or right hemisphere of brain using electroencephalography (EEG), and 3) the relationship between the dominance of visual space and hemisphere of brain. The proposed multi-robot system includes sequential and simultaneous actuations of robots dealing with single and multi-robot communication. Results indicate that most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Furthermore, computer vision has been used to address autism therapy through social robots that automatically adapt their behaviours. For example, researchers 110 113 have presented systems that simultaneously include eye contact, joint attention, imitation and emotion recognition for an intervention protocol for ASD children. Egger et al 114 presented the first study showing the feasibility of computer vision techniques to automatically code behaviours in natural environments.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, computer vision has been used to address autism therapy through social robots that automatically adapt their behaviours. For example, researchers 110 113 have presented systems that simultaneously include eye contact, joint attention, imitation and emotion recognition for an intervention protocol for ASD children. Egger et al 114 presented the first study showing the feasibility of computer vision techniques to automatically code behaviours in natural environments.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed therapy uses a NAO humanoid robot for ASD children. NAO is widely used for therapies in autism because of its anthropomorphic appearance [35], [36]. The robot is programmed to give three different kinds of stimuli to categorize the most effective stimulus for a particular level of autism.…”
Section: A Purpose Of Studymentioning
confidence: 99%
“…In special education, more specifically regarding Autism Spectrum Disorder (ASD) interventions, the ability of robots to improve the social and communication skills of children has been confirmed [3]. Numerous studies have demonstrated the use of social robots toward improving social skills such as joint attention [4][5][6]. Safety issues have also been considered [7].…”
Section: Introductionmentioning
confidence: 99%